Comparison of Hasson (Open) and Veress Needle (Closed) Technique of Creating Pneumoperitonium in Laparoscopic Cholecystectomy - Namra Shakoor, Sumera Naz, Muhammad Mudasser Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to compare the outcomes between hasson (open) and veress needle (closed) technique of creating pneumoperitonium in laparoscopic cholecystectomy. Study Design: Comparative/Randomized study Place and Duration: PHFMC (ZCD 417,Toba Tek Singh). Jun 2019-May 2020 Methods: Ninety patients of both genders with ages 20-75 years were presented in this study. All patients provided written informed consent before having their full demographic information collected, which included their age, gender, and body mass index. All the patients had symptomatic gall stones disease was underwent for laparoscopic cholecystectomy. Patients were categorized into two equal groups. Group I had 45 patients and received veress needle (closed) technique and group II received hasson (open) technique for creating pneumoperitoneum. Post-operatively outcomes in terms of access time , gas leak, visceral injury, vascular injury, need for conversion, umbilical port site hematoma, umbilical port site infection, umbilical port site hernia were assessed and compared among both groups. To analyze the entire set of data, we used the SPSS 24.0 edition. Results: Mean age of the patients in group I was 36.13 ±5.77 years with mean BMI 25.06 ±6.33 kg/m2 and in group II mean age was 37.23 ±6.55 years with mean BMI 25.16 ±4.45 kg/m2 . Majority of the patients 60 (30 in each group) were female. Mean access time in group II was lower 4.78 ±11.43 minutes as compared to group I 6.11±4.12 minutes. Mean closure time in group I was 7.33 ±7.23 minute and in group II mean closure time was 6.03±3.19 minutes. Frequency of gas leak in group I was higher found in 8 (17.8%) cases as compared to group II 3 (6.7%). Visceral injury was greater in group I 3 (6.7%) as compared to group II 1 (2.2%). Vascular injury among both groups was similar 2 (4.4%) and there is no any case found for conversion. Post-operatively complications hematoma, infection and umbilical hernia were greater in group II 4 (8.9%), 2 (4.4%) and 2 (4.4%) as compared to hasson (open) group. Conclusion: Pneumoperitonium was created more quickly and efficiently in laparoscopic cholecystectomy using the hasson (open) approach in this comparative analysis than any other method. When it comes to problems and injuries, the open approach (rather than the closed technique) was determined to be less risky overall.